(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2024)
Introduction: Multiple choice questions (MCQ) are very effective in assessing the students learning since it is very much objective and time saving. MBBS curriculum introduced MCQ in professional examination from 2002. Objective: This cross sectional descriptive study was conducted to get the teachers’ opinion about Pharmacology professional examination MCQ papers of different Universities of Bangladesh. Methods: For this purpose, opinions of total 56 purposively selected teachers of the Department of Pharmacology & Therapeutics of 20 Medical Colleges were collected through self-administered semi-structured questionnaire. Most of the teachers (61%) were in favour of existing distribution of different types of question in curriculum (recall-60%, understanding-30% and problem based-10%) for MCQ paper. Results: Majority of the teachers (71% and 63%) were satisfied with the present coverage of recall and understanding type questions respectively and 60% teachers were satisfied with the coverage of problem based type questions. Fifty-seven percent teachers were satisfied with content coverage in MCQ papers. About 57% teachers were satisfied with the construction of MCQs and 78% teachers were in favour of introduction of single best answer (SBA) type MCQ. Regarding introduction of negative marking for wrong answer, 61% were agreed with the proposal. Conclusion: Findings of this study may be used to redefine the distribution of different types question in SAQ papers and to improve the quality of question papers by ensuring their coverage and construction. JAFMC Bangladesh. Vol 19, No 1 (June) 2023: 6-10